CD19+ B-Cells, a New Biomarker of Mortality in Hemodialysis Patients - Molina, María; Allende, Luis M.; Ramos, Luis E.; Gutiérrez, Eduardo; Pleguezuelo, Daniel E.; Hernández, Eduardo R.; Ríos, Francisco; Fernández, Cristina; Praga, Manuel; Morales, Enrique (Frontiers in Immunology, 2018)
Background and objectives: Mortality of patients on haemodialysis (HD) remains very high despite recent improvements in HD techniques. Cardiovascular (CV) complications and infections are the main causes of death. Some studies suggest that disturbances in the immune system could play a role in this disproportionate mortality, through the links of immunity with inflammation and propensity to infections. However, few studies have addressed the role of lymphocyte populations and the global and CV mortality of HD patients. Aim: To analyze the relationship of Peripheral Blood Lymphocyte Populations (PBLP) and all-cause and CV mortality of HD patients. Design, setting, participants and measurements: We design a prospective observational single center study in a cohort of HD prevalent patients. PBLP were analyzed at baseline and after 1-year and patients were followed for a 5-year period. Main outcomes were all-cause and CV mortality. Results: One hundred and four patients (51% male, mean age 64.8 ± 15 years) were included. Follow-up was 18 (7-47) months. Fifty-five patients (52.8%) died, main causes of death being CVD (40%) and infections (29.1%). Low total lymphocyte counts were found in 47 patients (45.2%). 45.2% of patients had total lymphopenia, and the most frequency lymphopenias were CD19+ B-cell (57.7%), CD3+ (40.4%) and CD4+ (36.5%). After 1 year, all determinations were lower except CD56+CD16+CD3- Natural Killer. Patient survival was significantly lower in patients with a CD19+ B-cell count < 100 cells/µL at baseline as compared to patients with CD19+ B-cell > 100 cells/µL counts at the end of follow-up (16.5% vs 54%, p=0.003). By multivariable analysis, age, history of CV disease, Charlson index, a KT/V <1.2, and a CD19+ B-cell count <100 cells/μL at baseline and after 1-year were factors associated with of all-cause mortality. A CD19+ B-cell count < 100 cells/µL at baseline was associated with CV mortality. Conclusions: CD19+ B-cell lymphopenia is very common among HD patients and it could be an independent predictor of all-cause and CV mortality. More studies are needed to confirm these findings.